Experimental study on blasting with a short straight hole + wedge compound cut scheme in hard rock tunnels - Tu, Meng; Tang, Xianglong; He, Guidao; Peng, Songlin; Yang, Lin; Xu, Jinxing (Frontiers in Earth Science, 2025)
IntroductionIn drill-and-blast excavation for small- and medium-sized tunnels, the conventional wedge-cut blasting method is often constrained by the limited maneuvering space of construction equipment. This restriction can result in excessive inclination of wedge-cut holes relative to the tunnel face. Consequently, the rock in the cut zone is subjected to strong confinement, leading to reduced advance per round, low blasthole utilization efficiency, and an increased specific charge.MethodsIn this study, theoretical analysis and formula derivation were conducted to evaluate the respective advantages and limitations of wedge cutting and straight-hole cutting. Based on these analyses, optimal layout parameters for straight holes were determined. A combined short straight-hole + wedge compound cut blasting scheme was subsequently proposed and tested in a hard rock tunnel.ResultsWhen calculating the spacing between charge holes and relief holes, the influence of high strain rates on the rock’s tensile strength should be incorporated to ensure that theoretical parameters are both accurate and applicable. Compared with the original blasting scheme, the designed compound cut method increased the advance per round from 1.7–1.8 m to 2.0–2.1 m and improved blasthole utilization from 73.91%–78.26% to 86.96%–91.30%. The specific charge remained nearly unchanged, while detonator consumption decreased by approximately 0.4 detonators/m3, demonstrating clear economic benefits. The application of the short straight-hole + wedge compound cut technique also resulted in fewer remaining holes and finer rock fragmentation at the tunnel face, thereby enhancing the efficiency of muck removal and drilling operations in subsequent cycles.DiscussionThe short straight-hole + wedge compound cut technique has been successfully applied in small and medium-sized section hard rock tunnels,These results offer valuable guidance for optimizing drill-and-blast design parameters and construction practices in small- and medium-scale hard rock tunneling projects.